2017
DOI: 10.1038/s41598-017-02889-5
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cholesterolaemic effect of a consortium of probiotics: An acute study in C57BL/6J mice

Abstract: Hypercholesterolaemia is a major risk factor for cardiovascular disease and it has been found that some probiotic bacteria possess cholesterol-lowering capabilities. In this study, the ability of the Lab4 probiotic consortium to hydrolyse bile salts, assimilate cholesterol and regulate cholesterol transport by polarised Caco-2 enterocytes was demonstrated. Furthermore, in wild-type C57BL/6J mice fed a high fat diet, 2-weeks supplementation with Lab4 probiotic consortium plus Lactobacillus plantarum CUL66 resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 55 publications
(45 reference statements)
6
43
0
2
Order By: Relevance
“…In our study population, cholesterol and other plasma lipids were not significantly changed and support the observation that probiotic supplementation may have little impact in plasma lipids levels in healthy subjects 11 . However, in the hypercholesterolaemic SG3c subgroup (weight loss:1.47 kg), significant plasma LDL-C reductions of 0.4 mmol/L from baseline were detected in the probiotic group which supports the findings of our previous mouse studies with Lab4P 13 . A meta-analysis that assessed the impact of probiotics on lipid levels reported comparable changes in circulating LDL-C levels in hypercholesterolaemic subjects 41 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study population, cholesterol and other plasma lipids were not significantly changed and support the observation that probiotic supplementation may have little impact in plasma lipids levels in healthy subjects 11 . However, in the hypercholesterolaemic SG3c subgroup (weight loss:1.47 kg), significant plasma LDL-C reductions of 0.4 mmol/L from baseline were detected in the probiotic group which supports the findings of our previous mouse studies with Lab4P 13 . A meta-analysis that assessed the impact of probiotics on lipid levels reported comparable changes in circulating LDL-C levels in hypercholesterolaemic subjects 41 .…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that the presence of bacteria with bile salt hydrolase (BSH) activity can mediate the deconjugation of bile acids that has been implicated in the prevention of weight gain 39 . The Lab4P consortium has previously been shown to possess bile salt hydrolase activity 12,13 and in C57BL/6J mice fed a high fat diet www.nature.com/scientificreports www.nature.com/scientificreports/ with/without Lab4P, increased faecal deconjugated bile acid levels, reduced circulating cholesterol levels and reduced diet induced weight gain were observed in the Lab4P fed mice 13 . Bacterial BSH activity is also linked with the reduction of circulating cholesterol levels 40 .…”
Section: Discussionmentioning
confidence: 99%
“…and Lactobacillus spp. Supplementation with Lab4b has been shown to reduce the incidence of allergy in infants (Allen et al, 2010(Allen et al, , 2014 whilst Lab4 impacted on both inflammation (Davies et al, 2018;Garaiova et al, 2015;Hepburn et al, 2013) and metabolism (Michael et al, 2016(Michael et al, , 2017. Some probiotic bacteria are known producers of metabolites with neuromodulatory capability (Sarkar et al, 2016) and Lab4 has been shown to improve memory and alter brain metabolite profiles in aging rats (O'Hagan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…fermentum or L. ingluviei affect increase the body weight [181], and L. acidophilus NCDC 13 had no impact on obesity [182].…”
Section: Thus Bacterial Strains Have Different Probiotic Effects On mentioning
confidence: 93%